“It’s OKAY to not be Okay”- A link between childhood experiences and suicidal attempts among adults in Bikaner district, Rajasthan - Shandar Siddiqui,; Smita Rani Pradhan,; Ahmad Danish Rehan,; Asim Mustafa Khan,; Silpi Chatterjee,; MdKhalid Hassan, (International Journal of Psychosocial Rehabilitation, 2020)
Background: Adverse childhood experiences are associated with significant functional impairment and life loss in adolescence and adulthood. Exposure to multiple risk factors during childhood is associated with higher rates of depression, tobacco use, alcoholism, illicit drug use, and attempting suicide Objective: To through light on the possible relationship between childhood experiences and suicidal attempts during adulthood in a sample from Bikaner district, Rajasthan. Methods: This cross-sectional study was conducted in Bikaner district, Rajasthan during the period from JUNE 2019 through JUNE 2020. A random sampling technique was adopted to choose the participants in Bikaner district, Rajasthan. Childhood experiences were measured by applying a modified standardized Adverse Childhood Experiences International Questionnaire form. Suicidal attempt was measured by a question if there was any attempt for suicide during their previous life. Results: A total sample of 1000 individual was studied. The results revealed that forty one (4.1%) participants had history of suicidal attempts, suicidal attempts shows a strong positive association with mean score of household dysfunction and abuse (Cohen’s d = 0.72) and Positive history of suicidal attempts shows strong inverse association with mean score of bonding to family (as Cohen’s d = -1.04 which is considered as large effect size).Conclusion: It can be concluded from this study that suicidal attempts in our population are not uncommon, and may be more prevalent than many places. This might be an indicator for the repeated disastrous events that the people have experienced during the last few decades.